Republic of Belarus : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2011)
The Belarus authorities are moving in the direction of a flexible exchange rate system supported by an inflation-targeting (IT) regime, which would have significant benefits for the economy. A full-fledged IT framework (FFIT) requires a number of essential building blocks, which could be viewed as components of sound macroeconomic management. There are three additional features that could interfere with the IT regime. Some of the building blocks are essentially prerequisites for a successful launch of the IT regime; others could be developed (or fine-tuned) during early stages of IT implementation.